THE ESSENCE, CONTENT AND TYPES OF MARKETING ORGANIZATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the essence, content, and types of marketing organization in the context of modern business development. It analyzes different scientific approaches to marketing definitions, explores the historical evolution of marketing concepts, and investigates various organizational structures of marketing services in enterprises. The paper discusses the fundamental principles of marketing organization, the application of innovations, and future trends in marketing development. Special attention is paid to the analysis of modern marketing tools, including digital marketing and social media marketing, as well as the challenges faced by organizations in adapting to changing market conditions.